Portable Dual Mode Mobile Charger with Hand Crank Generator and Solar Panel - Md. Atiqur Rahaman; Nusrat Hoque; Nipu kumar Das; Farial Nur Maysha; MD Morshed Alam (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
A new method of charging a mobile phone with the help of hand crank generator, and solar panel is being presented in this paper. Solar panel is useful during daylight and hand crank generator can be used at night. So this is a dual mode charger which is operated in either way and both ways do not consume system power. This type of mobile charger is very useful when traveling because it uses solar panel to convert renewable source light into electricity. Mechanical hand crank generator is used which converts mechanical energy into electrical energy and then charges the mobile. No electrical sources are needed for it. Our design uses a compound gear train for transformation of the mechanical energy generated from the hand crank to the generator. For that reason it is convenient as well as economical to use such kind of mobile charger for our mobile phone.